PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN CORPORATE SOSIAL RESPONSIBILITY PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Ni Komang Apri Darma Anggreni; I Made Marsa Arsana (Universitas Triatma Mulya, 2020)
This study aims to obtain empirical evidence about the effect of profitability, company size, leverage, and the size of the board of commissioners on the disclosure of corporate social responsibility. This research is a quantitative research. The population in this study are mining companies listed on the Indonesia Stock Exchange for the period of 2016-2018. Data collection using annual financial reports (annual report). The number of samples in this study were 126 mining companies and were selected based on a purposive sampling method, which is a mining company that discloses corporate social responsibility. The analysis technique used is the classic assumption test, t test, F test and multiple linear analysis techniques with the help of SPSS version 25. The regression analysis technique shows Y = -2,217 + 0,809X1 + 0.090X2 + 0.071X3 + 0.119X4. The conclusion of the study shows that (1) Profitability has a partially positive and significant effect on the disclosure of corporate social responsibility. (2) Company size has a partially positive and significant effect on the disclosure of corporate social responsibility. (3) Leverage has a partially positive and significant effect on the disclosure of corporate social responsibility. (4) The size of the board of commissioners has a partially positive and significant effect on the disclosure of corporate social responsibility. and (5) profitability, company size, leverage and the size of the board of commissioners have positive and significant simultaneous effect on the disclosure of corporate social responsibility, it can be seen from the value of Adjusted R Square 81.4% corporate social responsibility influenced by independent variables while the remaining 18.6% influenced by other variables not included in the regression model.